FORGIVENESS DITINJAU DARI EMPATHY PADA PASANGAN SUAMI ISTRI DI KELURAHAN BINJAI KECAMATAN MEDAN DENAI - Rianda Elvinawanty (JURNAL TARBIYAH, 2016)
This study aims to examine the relationship between empathy and forgiveness. The hypothesis of this study is that there is a positive relationship between empathy and forgiveness, assuming that the higher the empathy, the higher the forgiveness. Conversely, the lower the empathy, the lower the forgiveness. Subjects of this study are married couples who live in Kelurahan Binjai, Kecamatan Medan Denai as many as 120 people or 60 couples, chosen by purposive sampling method. Data are obtained from a scale to measure empathy and forgiveness. The calculation is performed through the prerequisite test analysis (assumption test) that consists of normality test of distribution and linearity test. Data are analyzed used Pearson correlation technique through SPSS 21 for Windows. Results of the analysis of the data shows the correlation between empathy and forgiveness r = 0.847, p = 0.000. Thus, it can be concluded that empathy has significant relationship with forgiveness on the standard error test of 0.01 (one-tailed). The results show that the contribution (R2) given by empathy variable to forgiveness is 71.8 percent; the remaining of 28.2 percent is affected by other factors not examined. From these results, it can be concluded that the hypothesis of this study is accepted.Keywords : forgiveness, empathy